The narration of ego identity achievement in “The Beggar Maid” - Esfahani, Mehdi Hassanian; Talif, Rosli (Universiti Putra Malaysia Press, 2012)
Since the publication, Munro’s “The Beggar Maid: Stories of Flo and Rose” (1978) has been examined from various aspects, and more commonly considered to be a representation of social changes and/or feminist movements. In this paper and from a new perspective, the authors critically read the story as a narration of psychosocial development and ego identity achievement of its protagonist. Investigating the psychologically significant incidents that Rose, the heroine, undergoes provides the opportunity to justify “Epilogue”, the actual unpromising ending, compared to the potential cliché happy-ending some 20 pages before the last page. The theoretical framework consists of Eriksonian theory of psychosocial development, which maps the protagonist’s quest to find her ‘self’ and resolve her identity crisis, and Marcia’s theory of identity statuses which investigates the kinds of identity she develops into.